Pentingnya Pengucapan yang Jelas dari Orang Tua: Untuk Mengoptimalkan Fungsi Lobus Temporal pada Anak - Erni, Erni; khasisah, Fitri; Hawaniah, Aisyah (TSAQOFAH, 2024)
The brain is the primary organ responsible for maintaining human physical and psychological balance from developmental stages in the womb, through infancy, childhood, adolescence, adulthood, and old age. The brain guides humans to exhibit positive and negative behaviors. It functions positively in a positive environment and negatively in a negative one. A newborn's brain weighs 370 grams, and by the age of three, it reaches 70% of the adult brain weight, approximately 1.2 to 1.4 kilograms (3 pounds). This brain development phase is known as the "Golden Age." Parents or significant others raising children must understand that during early childhood, the brain develops rapidly. Neurons will function robustly and swiftly if provided with appropriate stimuli. This means that children will quickly understand, imitate, and memorize what they hear, see, and observe. Anyone raising a child, including educators and babysitters, must understand that the brain is a vital organ that needs protection from hard and sharp objects and must be safeguarded against severe impacts and deep injuries to prevent damage to brain growth and development. This study serves as a preliminary reference for understanding the brain's parts, demonstrating that the brain has various sections, each with its functions, as revealed by scientific research from neurologists.